Merger, Akusisi dan Konsolidasi dalam Perspektif Hukum Persaingan Usaha - Dwi Santo, Paulus Aluk Fajar (Binus Business Review, 2011)
Mergers, acquisitions and consolidation is a business strategy that is commonly used in the business world to be able to build competitive advantage company, which in time can enhance shareholder value while maximizing the prosperity of the company owners or shareholders. To achieve the above objective normative, policy-makers need a plan and steps of strategic and accurate information to avoid the risk of failure. However, the strategy of merger, acquisition and consolidation of certain potentially inhibit fair competition conditions, thus becoming one of the objects that need to be regulated in Law no. 5 Year 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. Market impact of mergers, acquisitions and consolidation is important for analysis because it can have significant legal consequences for businesses, so that the research method used is the juridical normative and empirical approaches. In practice of mergers, acquisitions and consolidation intersect with regulation in other sectors, especially banking and capital markets. That is, there should be equality of perception and interpretation among the institutions that issued the policy.